Ethnoscience-Project-Based Learning (E-PjBL) Model for Biology Education: Content and Construct Validity Analysis - Agus Muliadi; Joni Rokhmat; Aliefman Hakim; AA Sukarso (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to analyze the content and construct validity of the Ethnoscience–Project-Based Learning (E-PjBL) model for biology education in higher education. The study employed a Research and Development (R&D) approach guided by Nieveen’s educational design framework, focusing on the initial validation stage of model development. The validation process involved six expert validators with expertise in biology education, ethnoscience, instructional model development, and educational research. Research instruments consisted of content validity and construct validity validation sheets using a five-point Likert scale. The collected data were analyzed using descriptive quantitative analysis by calculating mean validity scores and inter-rater reliability using the percentage of agreement method. The results of the study indicate that: (1) the content validity of the E-PjBL model is categorized as very valid, with an overall mean score of 4.97, indicating that the model is developed based on actual learning needs and supported by state-of-the-art theoretical and empirical foundations; (2) the construct validity of the E-PjBL model is also classified as very valid, with an overall mean score of 4.91, demonstrating strong internal consistency among model components, including instructional syntax, learning objectives and impacts, as well as the learning environment and social system. These findings provide empirical evidence that the E-PjBL model is conceptually sound and theoretically feasible for further testing at the stages of practicality and effectiveness in higher education biology learning